In-Use Physicochemical Stability of Sandoz Rituximab Biosimilar in 0.9% Sodium Chloride Solution After Prolonged Storage at Room Temperature Conditions - Roman Borišek; André Mischo; Tobias Foierl (Drugs in R&D)
Abstract Background and Objective Often, stability studies do not cover all facets of ensuring patient safety for biologics, unless the impact of the in-use and out-of-fridge conditions is also assessed. This study investigated the physicochemical and biological stability of Sandoz rituximab biosimilar (SDZ-RTX). Methods In a worst-case setting, two SDZ-RTX batches in vials were exposed to long-term conditions (5 ± 3 °C) for at least the shelf-life period (36 months). These batches were exposed to out-of-fridge conditions of up to 25 ± 2 °C/60 ± 5% relative humidity in total for 14 days, and subsequently to 30 ± 2 °C/75 ± 5% relative humidity for 7 days. Thereafter, these batches were diluted to 1 mg/mL in 0.9% NaCl in 250-mL polyethylene infusion bags and stored at either 25 ± 2 °C/60 ± 5% relative humidity for 30 days or 30 ± 2 °C/75 ± 5% relative humidity for 14 days, representing in-use conditions. The stability of SDZ-RTX was assessed using a variety of analytical methods, including size-exclusion chromatography, cation exchange chromatography, non-reducing capillary electrophoresis sodium dodecyl sulfate, complement-dependent cytotoxicity-bioactivity, and subvisible particle count by light obscuration. Results Results for all assessments were within the stringent shelf-life acceptance criteria for SDZ-RTX for both batches under both in-use conditions. Conclusions These data show that the physicochemical and biological quality of SDZ-RTX diluted in 0.9% NaCl infusion bags is assured, even after prolonged worst-case (out-of-fridge and in-use) storage at elevated temperatures up to 30 °C, if the medication is prepared under aseptic conditions according to the Summary of Product Characteristics.